Establishing HR Practices-Employee Performance Relationship through Literature Survey - Jibrin-Bida, Mohammed; Abdul-Majid, Abdul Halim; Iyanda Ismail, Abdussalaam (Journal of Advanced Research in Business and Management Studies, 2020)
The success of any organization hinges on human resource of such organization. Human resource has the skills, knowledge and competencies required for the execution of organizational strategy and planning. Human resource is a crucial to the enhancement of sustainable competitive advantages and enhanced firm performance. Substantial numbers of HRM research have indicated positive effect of HR practices on employee performance. Yet, some other studies indicate the otherwise. Thus, the findings of the extant research are seemingly inconclusive. To address this issue, this paper, via an across-the-board literature survey, establish that HR practices involving recruitment and selection, training and development, compensation, performance appraisal, and succession planning impact employee performance. It can be discerned that the research findings that deny or cast doubt on the HRM-Performance nexus could not hold water, given the fact that there have been an overwhelming bulk of empirical studies that establish the link between HRM and performance. Hence, this research further proposes the five HR practices to be the determinant of employee performance. However, the proposed model can be empirically solidified further via collection and analysis of relevant data.